University Startups and Spin-Offs: Guide for Entrepreneurs in Academia - Stagars, Manuel (Springer, 2016)
University Startups and Spin-Offs teaches university students, researchers, and educators the most effective strategies and tactics for launching their own startups from academic platforms with the backing of school programs, public grants, incubators, seed accelerators, and private partnerships in all parts of the world.